2012
DOI: 10.1089/dia.2012.0059
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Diabetes in Asian Indians Based on Glycated Hemoglobin and Fasting and 2-H Post-Load (75-g) Plasma Glucose (CURES-120)

Abstract: In Asian Indians, use of A1c criteria would result in markedly higher prevalence rates of diabetes. It also identifies a different set of individuals with milder glucose intolerance and lower serum triglyceride levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 11 publications
3
23
1
1
Order By: Relevance
“…Other studies among Asian Indians, have also reported that, use of HbA1c criteria resulted in markedly higher prevalence of diabetes. 30 It is of interest to note that based on fasting glucose measurements alone, 36.9% of urban residents in three large South Asian cities have dysglycemia (14.9% with diabetes, 21.9% with prediabetes). If 2-hour post-load glucose measurements were done, an even higher proportion of the population would likely have dysglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies among Asian Indians, have also reported that, use of HbA1c criteria resulted in markedly higher prevalence of diabetes. 30 It is of interest to note that based on fasting glucose measurements alone, 36.9% of urban residents in three large South Asian cities have dysglycemia (14.9% with diabetes, 21.9% with prediabetes). If 2-hour post-load glucose measurements were done, an even higher proportion of the population would likely have dysglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…(2, 23, 24) Compared to other ethnic groups, South Asians have a higher prevalence of pre-diabetes and diabetes. (22, 2527) Since the MASALA study excluded individuals with cardiovascular disease, our prevalence estimates may be lower than in the overall population of middle-older aged US South Asians.…”
Section: Discussionmentioning
confidence: 99%
“…Iron deficiency anemia is highly prevalent in India, especially among women in the reproductive agegroup. Our earlier studies from the same Chennai Urban Rural Epidemiology Study (CURES) cohort used in this study (4), as well as another cohort, showed that the use of HbA 1c criteria, even in the absence of anemia, resulted in a markedly higher prevalence of diabetes compared with the use of the glucose values. Higher diabetes and prediabetes rates could have huge economic implications, leading to significantly higher health care costs.…”
mentioning
confidence: 76%
“…In the baseline of our CURES cohort, we assessed the prevalence of diabetes based on HbA 1c and fasting and 2-h glucose and reported that the use of HbA 1c criteria identifies a different set of individuals with milder glucose intolerance and lower serum triglyceride levels (4). Although this has some advantages in identifying individuals at an earlier stage in the natural history of the disease, it probably identifies individuals at lower cardiometabolic risk.…”
mentioning
confidence: 99%